The Limits of Electronic Fetal Heart Rate Monitoring in the Prevention of Neonatal Metabolic Acidemia. Issue 6 (June 2017) - Clark, Steven L.; Hamilton, Emily F.; Garite, Thomas J.; Timmins, Audra; Warrick, Philip A.; Smith, Samuel
Abstract : (Abstracted from Am J Obstet Gynecol 2017;216:163.e1–163.e6) Despite advances in technology and training, averting the neurologic injury causing hypoxia-induced fetal metabolic acidemia has not been demonstrated. By examining fetal heart rate tracings of infants with base deficit of more than 12 and base deficit of less than 8, this study seeks to assess the validity of electronic fetal heart rate monitoring (EFM) in preventing adverse metabolic acidemia–related outcomes and validate a fetal heart rate interpretation algorithm, specifically designed to assist with the management of category II fetal heart rate tracings.